DINAMIKA KONSEPTUALISASI PENDIDIKAN ILMU PENGETAHUAN SOSIAL (PIPS) DAN PENDIDIKAN KEWARGANEGARAAN (PKn) PADA PENDIDIKAN DASAR DAN MENENGAH (Suatu Telaah Collective Mindset dalam Ranah Historis-Epistemologis) - Udin Saripudin Winataputra; Sumanah Saripudin (LPPM Universitas Terbuka, 2011)
Generally, the conceptual framework of social studies in United States and in Indonesia includes concept and praxis of education in democracy which are organised in a form of (1) civic/citizenship education as one of the dimensions of goals, content, and processes of social studies; and (2) social studies education. Basically, education in democracy can also be deemed as a subsystem of social studies education, and social studies education. However, as a subsystem of education in democracy civic educationt has shown its uniqueness i.e. it sinergically focussed on the development of individuals potentials to become smart and good citizens. Along the line of the development of the ideals, instrumenst, and praxis of democracy civic/citizenship education has become the academic endeavour, which then is generally called as civic education or citizenship education.